The landform Deformation at the Iraq-Iran Border due to Earthquakes in the Period (2017-2018) - Sayyid, Baqer H.; Shaban, Auday H.; Abd, Najah A. (Iraqi Journal of Science, 2024)
The study targets to assess the potential of Interferometric Synthetic Aperture Radar (InSAR) in detecting ground distortion caused by earthquakes. The inSAR technique integrates Synthetic Aperture Radar (SAR) and interferometry to reveal the slightest changes on the earth’s surface through a specified period, impregnable to climate or time of day. The research analyses some scholarly articles to demonstrate the interest of InSAR in examining earthquakes and their outcome. These articles demonstrate the practical application of InSAR in enhancing fault slip analysis, ground deformation assessment, and early post-seismic changes in earthquakes. InSAR is beneficial with measurements from other tools, such as GPS and time series analysis, but it still offers valuable insights into earthquake characteristics and associated effects. The insights from these methodologies can help devise solutions to mitigate the impacts of earthquakes. In addition, the paper presents information about three earthquake swarm events and their corresponding fault types. The first event occurred on November 12th, 2017, while the second happened on November 25th, 2018. Despite their differences in magnitude and location, the second event was associated with a strike-slip fault. InSAR provides extensive practical applications, from natural hazard monitoring to infrastructure projects and topographic mapping.